Blockchain & supply chain, how to gain a competitive advantage? - Mkaouar, Hichem (2020)
New emerging technologies are becoming a vital source of competitive advantage. The aim of this paper is to determine the advantages of Blockchain in Supply chain, with a focus on food industry since quality and control are crucial.First, we identify the strengths and weaknesses of Blockchain and Supply chain business processes by analyzing their frameworks, and then we suggest a better framework that combines both concepts and offers a competitive advantage.We conclude that smart contracts and IoT play an important role in connecting the real world with the digital one, butmaking the implementation phase more challenging.